FEMINISM IN THE MOVIE MERINDU CAHAYA DE AMSTEL: SARRA MILLS DISCOURSE ANALYSIS - Marantika, Eka Ririn (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2024)
Abstract Feminism is always associated with everyday life, especially the female gender. Many media are used as a tool to convey feminism issues, one of which is film. Film or cinema is a mass media that is considered effective in expressing feminism issues that are presented neatly into an audio-visual story. Reflecting on this knowledge, the author will conduct a research on the issue of feminism. This research discusses feminism in a movie entitled Merindu Cahaya De Amstel by Hadrah Daeng Ratu released in 2022 with Sarra Mills' discourse analysis approach. The purpose of this research is to find out the representation of women in the movie Merindu Cahaya De Amstel. Qualitative descriptive method is used as an approach in this research. The results of this study show that Khadijah's character shows women as subjects and Kamila's character as objects. Where, what Khadijah did was a postmodern feminism movement stated by Cixous that women have the right to do what they want and voice it to the public sphere. Keywords: discourse analysis of Sarra Mills, feminism, Merindu Cahaya De Amstel Film